Thiolate-Initiated Synthesis of Dibenzothiophenes from 2,2′-Bis(methylthio)-1,1′-Biaryl Derivatives through Cleavage of Two Carbon–Sulfur Bonds - Masuya, Yoshihiro; Kawashima, Yuki; Kodama, Takuya; Chatani, Naoto; Tobisu, Mamoru (Synlett, 2019)
A catalytic reaction involving the cleavage of two carbon–sulfur bonds in 2,2′-bis(methylthio)-1,1′-biaryl derivatives is reported. This reaction does not require a transition-metal catalyst and is promoted by a thiolate anion. Notably, based on DFT calculations, the product-forming cyclization step is shown to proceed through a concerted nucleophilic aromatic substitution (CSNAr) mechanism.
Keywords: C–S cleavage; C–O cleavage; metathesis; thiophene